Santoro, Maurício. Brazil-China Relations in the 21st Century: The Making of a Strategic Partnership. 2022. Singapore: Springer Singapore Pte. Limited. 1st Edition, 139p. ISBN 9811903522 | Santoro, Maurício. Relações Brasil-China no século XXI: a construção de uma parceria estratégica. 2022. Cingapure: Springer Singapore Pte. Limited. 1a Edição, 139p. ISBN 9811903522 - de Souza Porto, Luis Filipe (Mural Internacional, 2023)
Maurício Santoro explores the role China has played in Brazil’s COVID pandemic era politics, carefully examining the participation of commodities in Sino-Brazilian trade and the environmental issues that arise. The literature on Brazil-China relations has expanded significantly during the last few years, however, most of the scholarship focuses mostly on trade and economic approaches. Santoro provides a new framework for understanding the current state of Sino-Brazilian relations in a changing world, bringing the reader an intelligent and conscientious example of diplomatic historical research that goes far beyond trade. For dealing with a profound and multifaceted approach, and presenting a broad perspective of this bilateral relationship, I consider the book “Brazil-China Relations in the 21st Century” as a pioneer for the study of Brazil relations with China. Keywords: Brazil. China. Sino Brazilian relations. RESUMO Durante o período da pandemia de Covid-19, Maurício Santoro explorou o papel político que a China desempenhou para o Brasil, examinando cuidadosamente a participação das commodities no comércio sino-brasileiro e as questões ambientais que surgiram ao longo da relação bilateral. A literatura sobre as relações Brasil-China expandiu-se significativamente durante os últimos anos, no entanto, a maioria dos estudos concentra-se principalmente em abordagens comerciais e econômicas. Santoro fornece uma nova estrutura para a compreensão do estado atual das relações sino-brasileiras em um mundo em transformação, trazendo ao leitor um exemplo talentoso de pesquisa histórica diplomática que vai muito além do comércio. Por tratar de uma abordagem profunda e multifacetada, e apresentar uma perspectiva ampla dessa relação bilateral, considero o livro “Relações Brasil-China no século XXI” como pioneiro no estudo das relações do Brasil com a China. Palavras-chave: Brasil. China. Relações sino-brasileiras. Recebido em: 05 mar. 2023 | Aceito em: 04 jul. 2023.